Efficient Peptide-Mediated In Vitro Delivery of Cas9 RNP - Oskar Gustafsson; Julia Rädler; Samantha Roudi; Tõnis Lehto; Mattias Hällbrink; Taavi Lehto; Dhanu Gupta; Samir EL Andaloussi; Joel Z. Nordin (MDPI AG, 2021)
The toolbox for genetic engineering has quickly evolved from CRISPR/Cas9 to a myriad of different gene editors, each with promising properties and enormous clinical potential. However, a major challenge remains: delivering the CRISPR machinery to the nucleus of recipient cells in a nontoxic and efficient manner. In this article, we repurpose an RNA-delivering cell-penetrating peptide, PepFect14 (PF14), to deliver Cas9 ribonucleoprotein (RNP). The RNP-CPP complex achieved high editing rates, e.g., up to 80% in HEK293T cells, while being active at low nanomolar ranges without any apparent signs of toxicity. The editing efficiency was similar to or better compared to the commercially available reagents RNAiMAX and CRISPRMax. The efficiency was thoroughly evaluated in reporter cells and wild-type cells by restriction enzyme digest and next-generation sequencing. Furthermore, the CPP-Cas9-RNP complexes were demonstrated to withstand storage at different conditions, including freeze-thaw cycles and freeze-drying, without a loss in editing efficiency. This CPP-based delivery strategy complements existing technologies and further opens up new opportunities for Cas9 RNP delivery, which can likely be extended to other gene editors in the future.